KINERJA TUTOR DALAM MENJALANKAN TUGAS POKOKNYA DI PKBM INSAN CENDEKIA PEKANBARU - Br Sitepu, Betania Jeniweri; Jas, Jasfar; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the performance of teachers in performing their main tasks in PKBM Scholar. Includes identifying learning needs, controlling curricula, executing the learning process, choosing methods and learning to implement according to the achievement domain (knowledge, attitudes and skills), motivating students, choosing, compiling or developing media / learning materials, managing learning activities and assessing learning outcomes. This study uses a descriptive naturalistic method with a qualitative approach aimed at knowing the performance of tutors in performing their main tasks. This study consists of one variable, namely the performance of tutors in performing their main tasks with 8 indicators, 22 sub-indicators. The subjects of this study were 3 people consisting of 1 key informant, 1 audit informant and 1 observer informant. Techniques used for data collection were observation, interviews and documentation. The data analysis technique uses data reduction, display data, data verification and triangulation. From the results of the research there are 3 indicators that are not in line with the main tasks of the tutor in accordance with the book with guidelines for package implementation of program programs, namely motivating students, package C tutors in PKBM Insan Cendekia not all of them perform their main tasks in motivating students. When choosing, compiling or developing media / learning materials package C, teachers at PKBM Insan Cendekia are still unable to properly choose or develop learning media. When assessing learning outcomes, there are some tutors who do not take daily tests, where daily tests are important when evaluating the results of teachers when teaching.Key Words: Performance, Tutor